Answer:
x^(1/2)
Explanation:
For this, we need to understand exponent rules. This one is like this, "A power to a power, you multiply the exponents". This is simply, because this expression would be equivalent to 3 base terms:
(x^(1/6))^3 = (x^(1/6)) * (x^(1/6)) * (x^(1/6))
And when you perform this multiplication "Powers of like bases, you add the exponents", you will get the following
(x^(1/6)) * (x^(1/6)) * (x^(1/6)) = x^(1/6 + 1/6 + 1/6) = x^(3/6) = x^(1/2)
Hence, this expression simplifies to x^(1/2).
Cheers.